Uporaba programa tracker za kinematično analizo gibanja športnikov - Marković, Marko (Šport (Ljubljana), 2013)
The development of modern computer technology, kinematic methods and expertisehas brought about an entirely new approach to the study of an athlete's motion. Progress in sport technology has lead to advancement in individual and team sports where technical perfection, along with other factors, is vitally important. The Tracker software enables investigation of kinematic parameters applied in the study of movement of athletes and their sport equipment in a two-dimensional space and through time dependence. By determining the direction of the two-dimensional coordinate system and the temporal relation of the video recording (dubbing) as well as calibrating the length, each selected point on the recording obtains real spatial and temporal coordinates. Moreover, the program is an excellent learning tool that can be used in PE lessons as a method of information and communication technology (ICT) or interdisciplinary curriculum which facilitates students' interactive learning and consequently increases their interest in the subject matter.
Keywords: gibanje; kinematics; kinematika; sport; sport training; šport; video analiza; video analysis